A novel animal model for residence time evaluation of injectable hyaluronic acid-based fillers using high-frequency ultrasound-based approach - Merola, Filomena (Clin Cosmet Investig Dermatol, 2018)
BACKGROUND: Hyaluronic acid (HA)-based devices are among the most popular filler agents for skin rejuvenation. One of the principal goals is the improvement in residence time of HA-based products, to increase their performance and reduce frequency of the treatment. So, understanding fillers, behavior after subcutaneous injection is a fundamental aspect for discovery and optimization of new products. Current in vivo approaches to detect/quantify injected HA fillers are not always well optimized or easy to apply. OBJECTIVE: To develop more efficacious and noninvasive diagnostic tools to make a quantitative evaluation of the degradation of fillers in a small animal model. MATERIALS AND METHODS: We evaluated the residence time of different HA-based fillers, fluorescein-labeled and not, injected subcutaneously in mice. Volumes of fillers were monitored through high-frequency ultrasound (HF-US) method while fluorescence intensity through the well-established fluorescence living imaging method. To confirm the effectiveness of HF-US, obtained volumetric measurements were compared with fluorescence intensity values. RESULTS: Both the presented methods revealed the same degradation kinetics for the tested products. CONCLUSION: The two used methods are fully comparable and quantitatively accurate. The presented approach has been proved to be noninvasive, sensitive, and reproducible.